THE IMPORTANCE OF QUALITY IN EDUCATION - Fernanda de Souza Oliveira, Audrey (Revista Gênero e Interdisciplinaridade, 2024)
This paper presents as a general objective the relationship between quality and its indicators, presenting the main challenges and strategies to promote quality in education, highlighting the importance of a holistic approach that takes into account not only the pedagogical aspects, but also the socio-emotional ones, cultural and technological. From this perspective, the different elements that contribute to the construction of quality education and the measures that can be adopted by educational institutions to achieve this desired objective will be discussed. Present the need to use quality indicators in education and teaching-learning environments by analyzing the benefits that these tools can bring to society, and highlighting their importance for 21st century education. The transformations caused by quality education are essential for the human, social, economic and democratic development of a society. Investing in improving education is investing in the future of a nation and its future generations. students, there is still a need to establish pedagogical access limits. If there is the possibility of access and a quality pedagogical proposal, the student becomes a professional and a competent citizen, with the skills required in this century and capable of applying the effective learning acquired.